IMPLEMENTATION OF GEOGRAPHIC INFORMATION SYSTEM TECHNOLOGY IN MAIL DELIVERIES ORGANIZATION - Desnica, Vladimir Janko; Šarac, Dragana (Journal of Applied Engineering Science, 2013)
The Post of Serbia should create conditions for improvement of its assortment of services by innovations of the current services and introduction of new commercial services in the work process. This can be achieved if high technologies – automation, mechanization and particularly information-communication technology and Geographic Information System (GIS) are introduced. The paper discusses results of the case study which comprises application of GIS on the example of delivery areas of the Post of Serbia in Novi Sad based on created thematic maps. The aim is to increase efficiency and productivity of delivery services by application of this technology.